DO GENETIC PERSONALITIES AND AUTHORATIVE PARENTING STYLES INFLUENCE CHILDREN’S CHARACTER? A CORRELATIONAL STUDY AT ELEMENTARY SCHOOLS IN INDONESIA - Dewiana Novitasari; Masduki Asbari; Agus Purwanto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This study aimed to examine the effects of genetic personality traits and parenting styles, particularly the authoritative parenting style, on children’s character development. The research employed a correlational design using a quantitative approach. Data were collected through online questionnaires distributed to respondents selected using a simple random sampling technique. The study population consisted of 150 parents of elementary school students. Data analysis was conducted using the Structural Equation Model (SEM) with SmartPLS version 3.0 software. The findings indicated that genetic personality and authoritative parenting style exerted a positive and statistically significant influence on children’s character development.